Surface Charging and Interfacial Water Structure of Amphoteric Colloidal Particles - Peukert, Wolfgang; Braunschweig, Björn; Sauerbeck, Christian (Journal of Physical Chemistry C, 2014)
Colloidal stability and adsorption processes at particle surfaces are controlled by the generation of surface charge and the molecular structure of the resulting electrical double layers. We have applied second-harmonic light scattering (SHS) to address doublelayer charging and the orientation of water molecules at surfaces of amphoteric particles in unprecedented detail. For that purpose we have performed the first SHS experiments of neat polystyrene particles with a mixture of sulfate (R−O−SO3-) and amino (R-NH2) functional groups. Changing the pH has a dramatic effect on the surface potential which can be tuned from positive to negative values and has allowed us to record changes in SHS signal while the isoelectric point of the particles is being crossed. The SHS signal is a function of two contributions which are directly related to the first molecular layer, its orientation, and to a second electric field induced contribution of the unidirectional field within the interfacial electric double layer. Through additional charge screening experiments we measured the surface charge density for positively as well as for negatively charged particle surfaces and confirmed the isoelectric point, where an increase in ionic strength had little effect on the SHS intensity. Furthermore, we have determined the net orientation of water molecules directly adsorbed to the particle surface from pH-dependent changes in the relative phase of the two SHS contributions.
Keywords: colloid; adsorption; particle; surface; charge; electric; ionic; strength; double; layer